Government measures in support of the financial sector in the EU and the United States - Stéphanie Marie Stolz; Michael Wedow (Intereconomics, 2011)
In the last issue of Intereconomics, a first article by the present authors looked into the measures that central banks have taken in support of the financial sector in an effort to mitigate the effects of the financial crisis. This second article describes the measures taken by governments to contain the impact of the financial crisis and discusses potential exit strategies. Although the focus is on the measures implemented by euro area governments, the article also compares these measures with the ones taken in the United Kingdom and the United States.
Keywords: 330